The some questions of customs logistics in Republic of Belarus (Journal of actual problems of jurisprudence, 2018)
In this article some questions of customs logistics in Republic of Belarus are considered. The author states a concept of customs logistics, the attention is paid to the purposes, tasks and rules of customs logistics. In article legislative steps for development of customs logistics in Republic of Belarus are analyzed. It is emphasized that the customs logistics is based on system of customs and tariff and non-tariff regulation. What the customs logistics integrates such important functions of customs activities as tariff regulating, information and analytical, check and financial and economic is noted. The author considers that questions of customs logistics are regulated generally by bylaws. One of the main bylaws regulating customs logistics at the moment is the Republican development program of logistic system and transit potential for 2016 – 2020. Key words: logistics, customs, Belarus, purposes, concept, law, bylaw, rules, activities.